Penataan Kelembagaan Pengujian Norma Hukum di Indonesia - Lailam, Tanto (Jurnal Konstitusi, 2018)
Artikel ini membahas tentang penataan kelembagaan pengujian norma hukum di Indonesia, yang diawali dengan pembahasan problematika kelembagaan dan praktik pengujian norma hukum saat ini dan gagasan penataaan lembaga kedepan. Hasil kajian menunjukkan bahwa beberapa persoalan, meliputi (1) kelembagaan yang tidak ideal dan tidak sesuai dengan checks and balances system, hal ini terbukti banyaknya lembaga yang terlibat dalam pengujian norma, yakni MK, MA, dan Mendagri–Gubernur (Wakil Pemerintah Pusat); (2) persoalan objek pengujian yang tidak memiliki batasan yang jelas; (3) dalam praktik, persoalan tolok ukur pengujian terjadi kerumitan, terutama dalam penggunaan tolok ukur dalam menilai pertentangan norma hukum. Gagasan penataan kelembagaan ini di desain untuk kelembagaan satu atap pada MK, yang didasari argumentasi bahwa: MK sebagai pengawal Pancasila dan UUD 1945, dalam rangka penataan kelembagaan yang berbasis pada mekanisme checks and balances system, mewujudkan hierarkisitas peraturan perundang-undangan yang berkelanjutan, implementasi pengujian formil dalam praktik pengujian peraturan perundang-undangan di bawah undang-undang, penataan regulasi menjadi lebih tersistem, pengujian produk hukum tertentu merupakan pintu masuk untuk melihat semua persoalan pertentangan normanya pada setiap hierarki. Pada sisi yang lain, objek dalam sistem pengujian peraturan perundang-undangan juga belum terintegrasi menurut konstitusi dan belum mengarah pada penataan sistem heirarki norma hukum dan upaya harmonisasi norma hukum. Sistem konstitusi dengan paradigma “the supreme law of the land” mengharuskan seluruh peraturan dibawahnya harus bersumber dan tidak boleh bertentangan, dengan berpijak pada prinsip “tidak boleh satu detik pun ada peraturan perundang-undangan yang berpotensi melanggar konstitusi tanpa bisa diluruskan atau diuji melalui pengujian yudisial”.This article is discussed the institutional arrangement of regulation reviews in Indonesia. It’s begins with a discussion of the institutional problems and practice of regulations review and the design of institutional arrangement in the future. The results of the study shows several issues including: (1) institutions which are not ideal and contradicted with checks and balances system, it’s proofed by amount of institutions has authority about the functions, namely: Judicial review (Constitutional Court, Supreme Court), and Executive Review (Minister of Home Affairs and Governor; (2) the object of review doesn’t clear boundaries; (3) in practice, the problems of standard reviews is complicated, especially in the use of judging standard in the conflict of legal norm. The idea of institutional arrangement is designed for one institutionalization at the Constitutional Court, which is based on the argument: The Constitutional Court as the guardian of the Pancasila (ideology of state) and the 1945 Constitution, in the framework of institutional arrangement based on checks and balances system, realizing the sustainable in the heirarchy of regulation, in practice of formal review to reviewing regulations under a law, arrangements of regulations more systematic and comprehsnsive, regulations review is the entrance to see all the issues of it’s conficting in each hierarchy. On the other hand, the object in the system of regulation reviews is also not integrated according by the constitution, and it’s not in accordance with the arrangement system in hierarchy of the regulation and efforts to harmonize the legal norms. The constitutional system with the “supreme law of the land” paradigm requires that all the regulations below should be sourced and not be contradictions, with the principle of “no regulations may be conflict againts the constitution without judicial review.